Effects of Dietary Ramie Powder at Various Levels on the Production Performance, Serum Biochemical Indices, Antioxidative Capacity, and Intestinal Development of Laying Hens - Wang, Xin; Liu, Yang; Zhao, Hao-Han; Wu, Yong-Mei; Liu, Chun-Jie; Duan, Guang-Ying; Wang, Yan-Zhou; Liu, Tou-Ming; Huang, Peng; Li, Ying-Hui; Fan, Zhi-Yong; Qiu, Hua-Jiao; et al. (Frontiers in Physiology, 2022)
The purpose of this study was to investigate the effects of ramie (0, 3, 6, and 9%) included in diets on production performance, antioxidative capacity, serum biochemical indices, and intestinal development of laying hens. A total of 432 Lohmann commercial laying hens were randomly allotted to one of four dietary treatments and fed for 6 weeks. The results showed that the inclusion of ramie had no negative effects on laying performance, and increased (quadratic, P < 0.05) the laying rate with the highest value in the 6% ramie group. However, ramie content in the diet up to 9% reduced the apparent metabolic energy, dry matter, and organic matter apparent digestibility of laying hens compared with those in the 3% ramie group. The content of high-density lipoprotein (HDL-C) in serum was increased (P < 0.05), but the activity of aspartate aminotransferase (AST) was decreased (P < 0.05) by dietary ramie supplementation. As the dietary ramie level increased, the activity of serum glutathione peroxidase (GSH-Px) was increased quadratically (P < 0.05). Compared with control, 3% ramie group significantly increased (P < 0.01) liver total superoxide dismutase (SOD) activity. Meanwhile, the addition of 3∼6% ramie powder increased (P < 0.05) villus height of jejunum and villus height/crypt depth (V/C) of ileum, which reflected the intestinal promotional effect of ramie powder. In conclusion, ramie in a diet of less than 9% might protect the liver and improve the antioxidative capacity with no detrimental impacts on the laying hens. Moreover, it could promote the intestinal mucosal structure and have a positive impact on the intestine health of the laying hens.